2019
DOI: 10.5978/islsm.28_19-or-03
|View full text |Cite
|
Sign up to set email alerts
|

The effect of antimicrobial photodynamic therapy against virulence genes expression in colistin-resistance <i>Acinetobacter baumannii</i>

Abstract: Background and Aims: The emergence of drug-resistant infections is a global problem. Acinetobacter baumannii has attracted much attention over the last few years because of resistance to a wide range of antibiotics. Applying new non-antibiotic methods can save lives of many people around the world. Antimicrobial photodynamic therapy (aPDT) technique can be used as a new method for controlling the infections. In this study we investigated the effect of aPDT on the expression of pathogenic genes in colistin-resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that the clearance rate of K. pneumoniae infection when treated with intravenous and nebulized polymyxin sulfate is higher than that with polymyxin sulfate alone. The combined use of intravenous injection and nebulization can also reduce the average intubation time and amount of polymyxin sulfate used during ICU hospitalization[ 33 ]. The main side effects of polymyxin include nephrotoxicity and neurotoxicity[ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the clearance rate of K. pneumoniae infection when treated with intravenous and nebulized polymyxin sulfate is higher than that with polymyxin sulfate alone. The combined use of intravenous injection and nebulization can also reduce the average intubation time and amount of polymyxin sulfate used during ICU hospitalization[ 33 ]. The main side effects of polymyxin include nephrotoxicity and neurotoxicity[ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Again, microorganisms can induce the overproduction of proteins involved in the repair of photodamaged DNA; however, some bacteria, such as Helicobacter pylori, possess only a few of such protective repair mechanisms [31]. Upon PDT treatment, ROS and 1 O 2 can modify bacterial gene expression profiles by modulating (i) the quorum sensing pathway, therefore inhibiting biofilm formation as shown in in vitro models, and/or (ii) the anti-virulence activities by reducing the gene expression of virulence factors in diverse clinical pathogens [32][33][34][35].…”
Section: Biological Effects Of Apdt: Potential Targets and Related Me...mentioning
confidence: 99%
“…Photodynamic therapy alone has been demonstrated to be ineffective in complete eradication of the pathogen, but synergistic effects along with antimicrobials such as gentamycin, imipenem, and colistin resulted in increased killing of PDR and XDR A. baumannii ( De Mello et al., 2019 ; Pourhajibagher et al., 2017 ; Wozniak et al., 2019 ). A study showed that A. baumannii , when treated with sublethal antimicrobial photodynamic therapy (aPDT) resulted in significantly increased expression of ompA, probably to compensate for its damage and enable bacterial survival ( Boluki et al., 2019 ). Besides antimicrobials, natural compounds such as chitosan have been studied in combination with PDT to effectively eradicate biofilm-associated A. baumannii cells ( Zhang et al., 2019 ; Fekrirad et al., 2021 ).…”
Section: Emerging Therapeutic Strategiesmentioning
confidence: 99%